Money laundering and terrorist financing activities and its prevention: a study on bKash’s AML&CFT department - Jyoti, Jerin Tasneem (Brac University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.